Peran ASEAN dan PBB dalam Mendorong Proses Demokratisasi di Myanmar Pasca Kudeta Militer 2021 - Hagi Mulya Sandhika (Departement of Mathematics Education, 2023)
It cannot be denied that democracy is one of the important issues in international relations. To assist countries that experience difficulties in implementing democratic principles in their countries, such as Myanmar, the Association of Southeast Asian Nations (ASEAN) and the United Nations (UN) as international organizations that are pro-democracy, have a responsibility to oversee the success of the process democratization, especially after the military coup that occurred on February 1, 2022. Data collection was carried out through a literature review of previous works as well as various official sources including statements, declarations and resolutions issued by ASEAN and the United Nations. From the results of this study it can be seen what efforts have been made by ASEAN and the United Nations in encouraging the communication process in Myanmar. Apart from that, this research also describes the differences and agreements in terms of the strategies used by these two international organizations in practice in the field. The author will also try to provide his personal views in this paper regarding which organizational approach is more effective in suppressing the Myanmar military junta regime.